The Response of Citronella Grass on Several NPKMg Fertlization Levels in Latosol Soil Type - Setiawan, NFN; Gusmaini, NFN; Nurhayati, Hera (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
Citronella grass (Cymbopogon nardus var genuinus L) is an essential oil-producing plant known as